(untitled) (Baghdad Science Journal, 2021)
Isolation of fungi was performed from February to July, 2019. One hundred clinical specimens were collected from King Abdullah Hospital (KAH) Bisha, Saudi Arabia. Samples were collected from twenty patients of different ages (30 - 70 years old) ten males and ten females. The samples were collected from patients with the two types of diabetics. Specimens included blood, hair, nail, oral swabs and skin. Specimens were inoculated on Sabourauds Dextrose agar containing chloramphenicol. Thirteen fungal species were isolated and identified. The isolated species were: Aspergillus flavus, A. niger, A. terrus, A. nidulans, A. fumigatus, Candida albicans, C. krusei, C. parapsilosis, C. Tropicalis, Curvularia lunata, Fusarium solani, Penicillium marneffei and Saccharomyces cerevisiae. Identification of molds was carried out morphologically and microscopically using available methods and books of identification, while identification of yeasts was carried out using API system. C. albicans recorded the highest isolated number where 31 colonies were isolated from 18 patients, representing relative density of 22.5%. (R. D.: is the number of a certain fungal species divided by the total number of fungi). Other isolated fungal species recorded relative density less than 16 %. The most common isolated fungus Candida albicans was molecularly identified using the 5.8S and flanking ITS regions. The antifungal activity of some natural essential oils (cinnamon, thyme, coconut, almond and clove) was assayed against isolated fungi using disk diffusion method. The used concentration was 5 µl / plate. The MIC values were also determined using different oil concentrations (1, 2.5, 5, 10, 20 and 40 µl / disc).